ANALISIS PERMASALAHAN MANAJEMEN OPERASIONAL PADA KULAKAN KOPI & GALERI LEMBANG - Arina, Darin; Charista, Azira Rizqi Charista; Fajrin, Jasmine Ramadhanti; Fadhilah, Fathia Izzah (Politeknik Pariwisata Medan, 2025)
Abstract This research aims to analyze operational management issues at Kulakan Kopi Galeri in Lembang using the APKL (Aktual, Problematik, Kekhalayakan, Layak) and USG (Urgency, Seriousness, Growth) approaches. A descriptive qualitative method was employed through observation, in-depth interviews, and analysis of primary data and documentation. Thematic analysis was used to identify key themes emerging from observational data, interviews, and documentation. The results show that the absence of written Standard Operating Procedures (SOPs) is the top priority, followed by weak branding, lack of signature menu items, mismatched price perception, and ineffective social media promotion. Based on USG analysis, these seven problems were mapped according to their urgency, seriousness, and growth potential. Therefore, strategic recommendations are proposed to improve operational performance and enhance the competitiveness of Kulakan Kopi Galeri.